Rula and Reba analysis on work postures: a case study at poultry feed manufacturing industry - Mahmood, Salwa; Syed Abdul Aziz, Syed Abd.Hafiz; Zulkifli, Mohd Zakwan; Marsi, Noraini (American Scientific Publishers, 2020)
Ergonomics in working industries play an important role which make any task being done easier, thus improving the company production quality. By applying the ergonomics systematically in working life, the work-related musculoskeletal disorders (WMSDs) can be reduced. WMSDs generally affect human body by working in awkward posture which gives discomfort and pain. The main objective of this study is to analyze the working postures. Next is to suggest the good working position for workers at poultry feed manufacturing industry by proposing standard operating procedure (SOP). The purpose is to reduce fatigue among workers with repetitive tasks. This study is carried out at poultry feed company located in Tanjung Langsat, Johor. Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) are the methodologies used to analyze the working postures of the workers. Videos and figures of the working postures will be recorded and being analyzed. Three selected workers are divided into three different tasks. From the analysis had been done, the score obtain for RULA method is 7, 6 and 7 for Workers 1, Workers 2 and Workers 3 respectively. Meanwhile for REBA method, the score is 12, 6 and 5 for workers respectively. Results show that the working postures is in high-risk level, which need to be considered. It is expected that this research will help by proposing proper SOP and work position for reducing the risk of WMSDs in industry. In regards, this research is expected to increase the awareness regarding on the good working postures among workers.